2011
DOI: 10.1002/cncr.25938
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic regulation and prognostic value of LAMP3 expression in breast cancer

Abstract: BACKGROUND: LAMP3 is a newly described hypoxia regulated gene of potential interest in hypoxia-induced therapy resistance and metastasis. The prognostic value of LAMP3 in breast cancer was investigated. METHODS: Expression levels of LAMP3 in breast cancer cell lines and patient tissues were determined by real-time polymerase chain reaction and in a tissue microarray by immunohistochemistry. Immunofluorescent staining was used to evaluate the distribution of LAMP3 in tumor xenografts relative to pimonidazole. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 32 publications
5
74
0
Order By: Relevance
“…The pattern of upregulated expression of Lamp3, PLD, and eNOS and decreased expression of SPARC is characteristic of cancer cell growth and metastasis. 48,49,51,67,68 Treating rats from the start of the SuHx protocol with MAZ51 ameliorated the developed PH and significantly reduced the number of obliterated pulmonary arterioles (Fig. 5), indicating to us that the elevated tissue levels of the isoforms VEGF-C and VEGF-D are contributing via VEGFR3 signaling to the process of lumen obliteration and perivascular inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…The pattern of upregulated expression of Lamp3, PLD, and eNOS and decreased expression of SPARC is characteristic of cancer cell growth and metastasis. 48,49,51,67,68 Treating rats from the start of the SuHx protocol with MAZ51 ameliorated the developed PH and significantly reduced the number of obliterated pulmonary arterioles (Fig. 5), indicating to us that the elevated tissue levels of the isoforms VEGF-C and VEGF-D are contributing via VEGFR3 signaling to the process of lumen obliteration and perivascular inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, Ozaki described it as TSC403 with the specific expression in the lungs and overexpression in breast cancer cells. Significant similarity to the other LAMP family proteins-LAMP1 and LAMP2, was observed [1].…”
Section: Introductionmentioning
confidence: 93%
“…LAMP proteins are highly glycosylated type 1 lysosomaltransmembrane glycoproteins [1] [2]. They are located mainly in the lysosomal membrane [3] and are rarely found on the surface of normal cells, most commonly occurring in cancer cells [1] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researches suggest that PERK/elfa has involved in hypoxia resistance and tumor growth. Nagelkerke et al 12 found in breast cancer that LAMP3 protein expression was established to be of prognostic relevance and was related with locoregional recurrence, tumor grade, size, lymph node, resistance to therapy, and steroid hormone receptor status. What's more, previous information suggested that LAMP3 expression was related with resistance to chemotherapy and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%